2D quasi-ordered nitrogen-enriched porous carbon nanohybrids for high energy density supercapacitors. Issue 19 (28th April 2016) - Kan, Kan; Wang, Lei; Yu, Peng; Jiang, Baojiang; Shi, Keying; Fu, Honggang
Abstract : 2D quasi-ordered nitrogen-enriched porous carbon (QNPC) nanohybrids have been synthesized by an in situ polymerization assembly method. The QNPC nanohybrids offer high specific capacitance, excellent rate-capability, long-term stability and high energy density. Abstract : Two-dimensional (2D) quasi-ordered nitrogen-enriched porous carbon (QNPC) nanohybrids, with the characteristics of an ultrathin graphite nanosheet framework and thick quasi-ordered nitrogen-doped carbon cladding with a porous texture, have been synthesized via an in situ polymerization assembly method. In the synthesis, the expandable graphite (EG) is enlarged by an intermittent microwave method, and then aniline monomers are intercalated into the interlayers of the expanded EG with the assistance of a vacuum. Subsequently, the intercalated aniline monomers could assemble on the interlayer surface of the expanded EG, accompanied by the in situ polymerization from aniline monomers to polyaniline. Meanwhile, the expanded EG could be exfoliated to graphite nanosheets. By subsequent pyrolysis and activation processes, the QNPC nanohybrids could be prepared. As supercapacitor electrodes, a typical QNPC12-700 sample derived from the precursor containing an EG content of 12%, with a high level of nitrogen doping of 5.22 at%, offers a high specific capacitance of 305.7 F g −1 (1 A g −1 ), excellent rate-capability and long-term stability. Notably, an extremely high energy density of 95.7 Wh kg −1 at a power density of 449.7 W kg −1 in an ionic liquid electrolyte can be achieved. The unique structural features and moderate heteroatom doping of the QNPC nanohybrids combines electrochemical double layer and faradaic capacitance contributions, which make these nanohybrids ideal candidates as electrode materials for high-performance energy storage devices.